Photosynthetic light-harvesting : Reconciling dynamics and structure of purple bacterial LH2 reveals function of photosynthetic unit - Sundström, Villy; Pullerits, Tõnu; van Grondelle, Rienk (Journal of Physical Chemistry B, 1999)
Great progress in the study of structure and dynamics of photosynthetic light-harvesting pigment-protein complexes has recently resulted in detailed understanding of the light-harvesting and light-conversion processes of photosynthesis. We review and discuss recent results on the elementary excitation transfer dynamics of the purple bacterial LH2 peripheral complex. When combining the information from the two LH2 structures that are now available with the experimental results obtained from steady-state spectroscopy, a variety of ultrafast techniques and computer simulations, a detailed understanding of the LH2 function is obtained. Dynamics relevant to the complete photosynthetic unit (PSU = LH2 + LH1 core + reaction center), as well as models of the PSU obtained on the basis of the LH2 structure, allow us to suggest how the characteristic structural features of LH2 and LH1 have been designed to optimize the overall light-harvesting and trapping process in the PSU.